Design, Synthesis, Crystal Structure, In Vitro and In Silico Evaluation of New N′-Benzylidene-4-tert-butylbenzohydrazide Derivatives as Potent Urease Inhibitors - Ahmad, Sajjad; Khan, Momin; Rehman, Najeeb Ur; Ikram, Muhammad; Rehman, Sadia; Ali, Mahboob; Uddin, Jalal; Khan, Ajmal; Alam, Aftab; Al-Harrasi, Ahmed (Molecules (Basel, Switzerland), 2022)
Background: Hydrazides play a vital role in making biologically active compounds in various fields of chemistry. These determine antioxidant, antidepressant, antimalarial, anti-inflammatory, antiglycating, and antimicrobial activity. In the present study, twenty-three new N′ benzylidene-4-(tert-butyl)benzohydrazide derivatives (4–26) were synthesized by the condensation of aromatic aldehydes and commercially available 4-(tert-butyl)benzoic acid. All the target compounds were successfully synthesized from good to excellent yield; all synthesized derivatives were characterized via spectroscopic techniques such as HREI-MS and 1H-NMR. Synthesized compounds were evaluated for in vitro urease inhibition. All synthesized derivatives demonstrated good inhibitory activities in the range of IC50 = 13.33 ± 0.58–251.74 ± 6.82 µM as compared with standard thiourea having IC50 = 21.14 ± 0.425 µM. Two compounds, 6 and 25, were found to be more active than standard. SAR revealed that electron donating groups in phenyl ring have more influence on enzyme inhibition. However, to gain insight into the participation of different substituents in synthesized derivatives on the binding interactions with urease enzyme, in silico (computer simulation) molecular modeling analysis was carried out.